7T bone perfusion imaging of the knee using arterial spin labeling MRI. Issue 5 (24th December 2019) - Li, Xiufeng; Johnson, Casey P.; Ellermann, Jutta
Abstract : Purpose: To evaluate the feasibility of arterial spin labeling (ASL) imaging of epiphyseal bone marrow in the distal femoral condyle of the knee at 7T MRI. Methods: The knees of 7 healthy volunteers were imaged with ASL using a 7T whole body MRI scanner and a 28‐channel knee coil. ASL imaging used a flow‐sensitive alternating inversion recovery method for labeling and a single‐shot fast spin echo sequence for image readout. ASL imaging with a single oblique transverse slice was performed at 2 slice positions in the distal femoral condyle. Blood flow was measured in 2 regions of interest: the epiphyseal bone marrow and the overlying patellofemoral cartilage. To analyze perfusion SNR, 200 noise images were also acquired using the same ASL imaging protocol with RF pulses turned off. Results: Knee bone marrow perfusion imaging was successfully performed with all volunteers. The overall mean of blood flow in the knee bone marrow was 32.90 ± 2.41 mL/100 g/min, and the blood flow was higher at the more distal slice position. We observed significant B0 and B 1 + inhomogeneities, which need to be addressed in the future to improve the quality of ASL imaging and increase the reliability of knee bone marrow perfusion measurements. Conclusion: Bone marrow perfusion imaging of the distal femoral condyle is feasible using ASL at 7T. Further technical development is needed to improve the ASL method to overcome existing challenges.